1977
DOI: 10.1063/1.434936
|View full text |Cite
|
Sign up to set email alerts
|

The vibrational spectrum and lattice dynamics of polycrystalline ammonium hydrosulfide

Abstract: The infrared spectra of NH4HS and ND4DS have been recorded from 200 to 4000 cm−1 at liquid nitrogen temperatures, and the Raman spectra of these substances have been recorded from 0 to 4000 cm−1 over the temperature range 83–390°K. No evidence of a second solid phase was obtained. Internal and external fundamentals were assigned, in detail, based on selection rules, isotopic frequency shifts, and analogy with other structurally similar salts. Barriers to anion and cation reorientation of 3.8 and 1.9 kcal/mole,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

1977
1977
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
1
19
1
Order By: Relevance
“…See Fig. 1 of Bragin et al (1977) for an illustration of the unit cell of crystalline NH 4 SH based on the work of West (1934). Several observations argue for a high purity of our NH 4 SH ices.…”
Section: Synthesis and Spectroscopy Of Nh 4 Shmentioning
confidence: 93%
See 3 more Smart Citations
“…See Fig. 1 of Bragin et al (1977) for an illustration of the unit cell of crystalline NH 4 SH based on the work of West (1934). Several observations argue for a high purity of our NH 4 SH ices.…”
Section: Synthesis and Spectroscopy Of Nh 4 Shmentioning
confidence: 93%
“…The earliest IR work appears to be that of Bragin et al (1977) who showed a single spectrum at 98 K of the crystalline solid. Aside from it having a few small extra absorptions at 1750-1500 cm À1 , and showing traces of trapped NH 3 , that spectrum agrees with our Fig.…”
Section: Synthesis and Spectroscopy Of Nh 4 Shmentioning
confidence: 97%
See 2 more Smart Citations
“…But as noted above most of the uncertainty in the measurements is in AS for the reaction. The other possible source of error in extrapolation would be a phase change in NH4SH, but Bragin et al (1977) did not see evidence for one down to 83 K. In view of all of the above, we favor our calculations with the strongly enriched mixing ratios, reserving our doubts about Kp until improved laboratory data become available.…”
Section: Errors In the Equilibrium Constant?mentioning
confidence: 99%